Cross-Cultural Pastoral: The Practice of Indoor Grave Traditions - Lorameng, Sastrilya Asye; Mawuntu, Marhaeni Luciana (Jurnal Indonesia Sosial Sains, 2025)
The Sangihe tribe of North Sulawesi practices indoor graves as a hereditary tradition, perceived as natural and harmonious with daily life. Despite its cultural significance, this practice raises questions about its alignment with Christian teachings and modern norms. This study explores how the GMIST Getsemani Salurang congregation reconciles the tradition with faith, aiming to develop a cross-cultural pastoral model that respects local wisdom while fostering theological reflection. A qualitative case study approach was employed, with data collected through interviews with congregants (e.g., Inyong, 60; Andri, 72) and analysis of church practices. Thematic analysis was guided by Niebuhr’s "Christ and Culture" framework. Indoor graves are viewed as acts of familial love and respect, not ritualistic worship. The church adopts a transformative pastoral approach, balancing cultural preservation with theological discernment. The research offers a model for religious institutions to mediate tradition and modernity, emphasizing cultural sensitivity in pastoral care. It contributes to broader discussions on indigenous-Christian syncretism in Indonesia.